Koronawirus jako problem teologiczny : dobroć Boga a cierpienie świata - Beyga, Paweł (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
One of the most important questions in the theological and philosophical debate are pain in the human life and God’s providence. The science looks at the coronavirus in the medical, biological and many other perspectives. The article shows the pandemic as a theological problem. The author of the text looked at the problem of human pain and providence of God in the theological, biblical and liturgical perspective. The problem of the article is a problem that is present at all times, so it does not lose anything of its relevance.
Keywords: coronavirus; pain; theology; providence